Comparative finite element analysis of internal root resorption treatment using various root canal filling materials - Eskibaglar, Busra Karaagac; Erdem, Serkan; Eskibaglar, Mehmet; Kaman, Mete Onur (Bmc, 2026)
Background This study evaluated the stress distribution in maxillary incisors with internal resorption (IR) filled with various root canal filling materials using finite element analysis (FEA). Methods A three-dimensional model of the maxillary central incisor was generated by scanning. Twenty-seven models were created using different materials to fill the IR area in the apical, middle, and coronal third of the teeth. The root canals of the IR defect models were filled with mineral trioxide aggregate (MTA), Biodentine, bioceramic sealer (BCS), gutta percha (GP), or their combinations. FEA was used to evaluate the stress distribution in the IR maxillary incisors. To simulate masticatory force, 100 Newtons was applied at an angle of 130o to the palatal surface of the tooth. The von Mises(vM) stress criteria were used to compare the mechanical properties of the root canal filling materials, the vM stress criteria were used. Results The maximum vM stress values measured within the IR defect region were the lowest in the models completely filled with GP, whereas the highest stresses occurred in the models completely filled with Biodentine. In IR models filled with calcium silicate-based root canal filling materials or combinations thereof, vM stresses were more homogeneously distributed and lower than those in models filled completely with GP. Conclusion The use of calcium silicate-based root canal filling materials or their combinations may contribute to a more favorable biomechanical behavior in teeth affected by IR.
Keywords: Bioceramic sealer; Biodentine; Finite element analysis; Internal resorption; Mineral trioksite aggregate